Estilos de ensino de professores no Equador no contexto COVID-19 - Zambrano Vacacela, Luis Leonardo (Journal of Learning Styles, 2021)
This research starts from a non-experimental, transactional quantitative design with a descriptive scope, aims to identify the teaching style of teachers in Ecuador in the context of a health emergency COVID-19. In collaboration of 485 teachers between 20 to 60 years of age, who work at the initial, primary and secondary level of public and private establishments of the urban and rural sector of the Intercultural and Intercultural Bilingual System participate in the single-teacher, multi-teacher and complete types. The instrument used is the Teaching Styles Questionnaire through an online application. The results show that the predominant style in educators is the Functional followed by the Open, but with very little inclination for the Structure and Formal, in addition, that these are related to the sector, the level and the type of institution in which teaching is taught, but they do not correspond to sex, age and the educational system.
Keywords: Teaching Styles; teachers; Ecuador; COVID-19